Agricultural disaster management and contingency planning to meet the challenges of extreme weather events (MAUSAM, 2016)
Natural disasters of hydro-meteorological nature are playing a key role in the economic development of India. Agricultural production in India is largely dependent on the performance of summer monsoon rainfall. Apart from its spatial and temporal variability, several climatic anomalies / extremes attaining disastrous form at times were found to influence the country's agricultural production. Nature and magnitude of climate extremes that frequent India are presented with their history and region of occurrence.  Droughts and floods are found to be paramount. Of late, hailstorms, cold and heat wave conditions are also exerting considerable influence on field and orchard crops. Trends in extreme events, their frequency and effects on crops are discussed. Regions in the country prone to be sensitive to the various weather extremes are presented. Management strategies and contingency planning to be adopted to cope-up the weather extremes are elucidated. Few case studies on the successful strategies adopted at the field level to cope-up extreme weather events under National Initiative on Climate Resilient Agriculture (NICRA) program are reported.